Aggregate stability and organic carbon stock under different land uses integrally regulated by binding agents and chemical properties in saline‐sodic soils. (19th August 2021) - Feng, Haojie; Wang, Shunyi; Gao, Zideng; Pan, Hong; Zhuge, Yuping; Ren, Xueqin; Hu, Shuwen; Li, Chengliang
Abstract: Aggregate stability and soil organic carbon (SOC) are critical for maintaining soil structure and preserving soil productivity. Land use substantially affects the process of soil aggregate stabilization and SOC sequestration, yet the detailed mechanisms have not been well studied in degraded soil ecosystems (e.g., saline‐sodic soils). Therefore, to interpret the effects of land‐use changes on soil aggregate stability and SOC stocks in saline‐sodic soils, soils were sampled from four major land‐use areas (degraded meadow, artificial forest, sorghum field, and paddy field) in Northeast China. The results showed that artificial forest soils exhibited the greatest proportion of water‐stable aggregate (>250 μm) in 0–10 and 10–20 cm layers than sorghum and paddy field, which was mainly due to the absence of tillage disturbance. The highest SOC stock (59.79 Mg ha −1 ) was observed in paddy soils, indicating its greater SOC sequestration potential than those of other land uses. The variance partition analysis (VPA) revealed that soil parameters resulted in 85.1% variation regarding soil aggregate stability, in which the chemical characteristics (i.e., pH, EC, exchangeable Na +, and exchangeable sodium percentage) contributed 23.1%, binding agents (SOC, exchangeable Ca 2+, and poorly crystalline Fe/Al oxides) contributed 20.6%, and their interactions contributed 39.5%. Binding agents directly participated in soil aggregation processes by forming clay‐polyvalent metal complexes, while the chemical characteristics indirectly promoted soil aggregation via increasing various binding agents. Understanding the interactions between binding agents and clay are important for promoting soil aggregate stabilization in saline‐sodic soil.